Mast Cell Degranulation Exacerbates Skin Rejection by Enhancing Neutrophil Recruitment - Ngo Nyekel, Flavie; Pacreau, Emeline; Benadda, Samira; Msallam, Rasha; Åbrink, Magnus; Pejler, Gunnar; Davoust, Jean; Benhamou, Marc; Charles, Nicolas; Launay, Pierre; Blank, Ulrich; Gautier, Gregory (Frontiers in Immunology, 2018)
Recent evidences indicate an important role of tissue inflammatory responses by innate immune cells in allograft acceptance and survival. Here we investigated the role of mast cells (MC) in an acute male to female skin allograft rejection model using red MC and basophil (RMB) mice enabling conditional MC depletion. Kinetic analysis showed that MCs markedly accelerate skin rejection. They induced an early inflammatory response through degranulation and boosted local synthesis of KC, MIP-2 and TNF. This enhanced early neutrophil infiltration compared to a female-female graft-associated repair response. The uncontrolled neutrophil influx accelerated rejection as antibody-mediated depletion of neutrophils delayed skin rejection. Administration of cromolyn, a MC stabilizer and to a lesser extent ketotifen, a histamine type I receptor antagonist, and absence of MCPT4 chymase also delayed graft rejection. Together our data indicate that mediators contained in secretory granules of MC promote an inflammatory response with enhanced neutrophil infiltration that accelerate graft rejection.